Macroeconomic News and Stock–Bond Comovement - Duffee, Gregory R (Review of Finance, 2023)
Abstract Covariances between aggregate stock returns and changes in bond yields change sign over time. Existing theories emphasize either time-varying properties of expected inflation or time-varying properties of real yields. Using revisions in survey forecasts as proxies for macroeconomic news, neither approach succeeds empirically. Inflation-centric models require much more news about expected future inflation than we observe from surveys. Real-centric models posit signs of covariances among macroeconomic news, changes in yields, and stock returns that do not match those in the data. In a nutshell, macroeconomic news appears to drive a substantial part of stock–bond comovement, but not in ways consistent with our theories.